Hematopoietic Stem Cell Transplantation for Neurological Disorders: A Focus on Inborn Errors of Metabolism - de Vasconcelos, Pedro; Lacerda, João F. (Frontiers in Cellular Neuroscience, 2022)
Hematopoietic stem cells have been investigated and applied for the treatment of certain neurological disorders for a long time. Currently, their therapeutic potential is harnessed in autologous and allogeneic hematopoietic stem cell transplantation (HSCT). Autologous HSCT is helpful in immune-mediated neurological diseases such as Multiple Sclerosis. However, clinical benefits derive more from the immunosuppressive conditioning regimen than the interaction between stem cells and the central nervous system. Mainly used for hematological malignancies, Allogeneic HSCT explores the therapeutic potential of donor-derived hematopoietic stem cells. In the neurological setting, it has proven to be most valuable in Inborn Errors of Metabolism, a large spectrum of multisystem disorders characterized by congenital deficiencies in enzymes involved in metabolic pathways. Inborn Errors of Metabolism such as X-linked Adrenoleukodystrophy present with brain accumulation of enzymatic substrates that result in progressive inflammatory demyelination. Allogeneic HSCT can halt ongoing inflammatory neural destruction by replacing hematopoietic-originated microglia with donor-derived myeloid precursors. Microglia, the only neural cells successfully transplanted thus far, are the most valuable source of central nervous system metabolic correction and play a significant role in the crosstalk between the brain and hematopoietic stem cells. After transplantation, engrafted donor-derived myeloid cells modulate the neural microenvironment by recapitulating microglial functions and enhancing repair mechanisms such as remyelination. In some disorders, additional benefits result from the donor hematopoietic stem cell secretome that cross-corrects neighbouring neural cells via mannose-6-phosphatase paracrine pathways. The limitations of allogeneic HSCT in this setting relate to the slow turnover of microglia and toxicities such as graft-vs-host disease. These restraints have accelerated the development of hematopoietic stem cell gene therapy, where autologous hematopoietic stem cells are collected, manipulated ex vivo to overexpress the missing enzyme, and infused back into the patient. With this cellular drug vehicle strategy, the brain is populated by improved cells and exposed to supraphysiological levels of the flawed protein, resulting in metabolic correction. This review focuses on the current applications of HSCT and gene therapy for the treatment of central nervous system diseases, emphasizing the underlying mechanisms that result in brain repair.